Conventional vs accelerated beef production for traditional and later-maturing cattle types - Myers, S.M.; Dikeman, Michael E.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Analysis of traditional and later-maturing cattle types fed under accelerated (placed directly on the finishing ration) and conventional (back grounded on a growing ration before finishing) system, indicated large differences between feeding systems but smaller differences between cattle types in the same feeding system. Differences between feeding systems stress the economic importance of maintaining maximum gain, and the disadvantages of extended feeding periods, when much of the feed consumed is required for maintenance. Later-maturing cattle on accelerated feeding required the least feed per pound of gain.
Keywords: Beef; Feeding systems; Gain